Clinical‐Grade Human Multipotent Adult Progenitor Cells Block CD8+ Cytotoxic T Lymphocytes. (27th July 2016) - Plessers, Jeroen; Dekimpe, Emily; Van Woensel, Matthias; Roobrouck, Valerie D.; Bullens, Dominique M.; Pinxteren, Jef; Verfaillie, Catherine M.; Van Gool, Stefaan W.
Abstract : This study assessed the in vitro influence of a clinical‐grade human multipotent adult progenitor cell (MAPC) product (MultiStem) on the cytotoxic function of CD8 + T cells (CTLs) by evaluating the immunogenicity of MAPCs and the susceptibility of MAPCs toward CTL‐mediated lysis and by analyzing the mechanism of MAPC‐mediated modulation of CTL functionality. These MAPCs were found to be an immune‐modulating population that inhibits CTL activation and effector responses. Abstract : Acknowledgements: MultiStem cells are clinical‐grade multipotent adult bone marrow‐derived progenitor cells (MAPCs), with extensive replication potential and broader differentiation capacity compared with mesenchymal stem cells. Human MAPCs suppress T‐cell proliferation induced by alloantigens and mutually interact with allogeneic natural killer cells. In this study, the interaction between MultiStem and CD8 + cytotoxic T lymphocytes (CTLs) was addressed for the first time. In an in vitro setting, the immunogenicity of MultiStem, the susceptibility of MultiStem toward CTL‐mediated lysis, and its effects on CTL function were investigated. MultiStem was nonimmunogenic for alloreactive CTL induction and was—even after major histocompatibility complex class I upregulation—insensitive to alloantigen‐specific CTL‐mediated lysis. Furthermore, MultiStem reduced CTL proliferation and significantly decreased perforin expression during the T‐cell activation phase. As a consequence, MultiStem dose‐dependently impaired the induction of CTL function. These effects of MultiStem were mediated predominantly through contact‐dependent mechanisms. Moreover, MultiStem cells considerably influenced the expression of T‐cell activation markers CD25, CD69, and human leukocyte antigen‐DR. The MultiStem‐induced CD8 − CD69 + T‐cell population displayed a suppressive effect on the induction of CTL function during a subsequent mixed‐lymphocyte culture. Finally, the killer activity of activated antigen‐specific CTLs during their cytolytic effector phase was also diminished in the presence of MultiStem. This study confirms that these clinical‐grade MAPCs are an immune‐modulating population that inhibits CTL activation and effector responses and are, consequently, a highly valuable cell population for adoptive immunosuppressive therapy in diseases where damage is induced by CTLs. Because multipotent adult progenitor cells (MAPCs) are among the noteworthy adult mesenchymal stem cell populations for immune therapy and have the advantage over mesenchymal stem cells (MSCs) of large‐scale manufacturing and banking potential and thus prompt availability, it is important to understand how MAPCs interact with immune cells to validate their widespread therapeutic applicability. Cytotoxic immune effector cells play a crucial role in immune homeostasis and in the pathogenesis of some autoimmune diseases. This study assessed for the first time the in vitro influence of a clinical‐grade human MAPC product (MultiStem) on the cytotoxic function of CD8 + T cells (CTLs) by evaluating the immunogenicity of MAPCs and the susceptibility of MAPCs toward CTL‐mediated lysis and by analyzing the mechanism of MAPC‐mediated modulation of CTL functionality. These results may represent a highly relevant contribution to the current knowledge and, in combination with the results of future phase II/III trials using MultiStem, could lead to an intriguing continuation of stem cell‐based research for immunotherapy.